2022
DOI: 10.1063/5.0079535
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile reconfigurable broadband photodiodes based on BP/α-In2Se3 ferroelectric p–n junctions

Abstract: Imagers with pre-processing functions, such as image recognition and classification, contrast enhancement, and noise reduction, play a critical role in the neuromorphic visual system. Optoelectronic plasticity is a prerequisite to achieve these functions. In this study, we demonstrate a nonvolatile reconfigurable broadband photodetector based on a ferroelectric heterostructure composed of BP (black phosphorus)/α-In2Se3. The plasticity of the device comes from the ferroelectric polarization of α-In2Se3 that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The reason is the reversal of the stacking order, which will change the relative direction between built-in potential and polarization state, thus leading to the enhancement or reduction of the photovoltaic performance. [23,52] The stability of the short-circuit current density reflects the stability of the polarization state. We compared the short-circuit current densities (in both the polarization states) for the 1st and 1000th cycles in Figure 4b and found that the magnitude of the current density barely changed.…”
Section: Resultsmentioning
confidence: 99%
“…The reason is the reversal of the stacking order, which will change the relative direction between built-in potential and polarization state, thus leading to the enhancement or reduction of the photovoltaic performance. [23,52] The stability of the short-circuit current density reflects the stability of the polarization state. We compared the short-circuit current densities (in both the polarization states) for the 1st and 1000th cycles in Figure 4b and found that the magnitude of the current density barely changed.…”
Section: Resultsmentioning
confidence: 99%
“…Strong light-matter interaction and ultrafast charge transfer in vdW heterostructures 143 have attracted considerable attention for high-performance photodetector applications. 119,[144][145][146] By employing ferroelectric 2D semiconducting materials 147,148 or utilizing the oxidation property of BP for charge trap, 149 nonvolatile photodetectors can be further constructed. This provides new concepts for optoelectronic memory as well as for synaptic development in the visual system.…”
Section: Light-triggered Modementioning
confidence: 99%
“…[61] In addition to the neuromorphic electronic and spintronic devices, low-dimensional heterostructures exhibit some optoelectronic properties inaccessible in bulk heterostructure, and also show great potential in the design of neuromorphic optoelectronic devices. [11,15,16,[62][63][64][65][66] The study of neuromorphic optoelectronic computing can be tracked back to late 1980s, when Caver Mead proposed to use the inherent physical properties of siliconbased device to design the retinormophic sensor. [67] Later, metal/ semiconductor diodes were used to process detected images with assist of spatial light modulator and analog memory.…”
Section: Introductionmentioning
confidence: 99%